Vaginal Evisceration of Small Bowel With Extraperitoneal Ileal Resection of the Herniated Loops: A Case Report - Missori, Giulia; Marchesini, Nicolò Luigi Arrigo; Mosca, Donatella; Ricciardolo, Andrea Aurelio; Serra, Francesco; Gelmini, Roberta (Frontiers in Surgery, 2022)
INTRODUCTION: Vaginal evisceration is an extremely rare surgical emergency that can be described as the extrusion of abdominal viscera through a defect or a rupture of the vaginal wall. We reported the case of an acute abdomen due to small bowel evisceration secondary to vaginal vault dehiscence that required combined vaginal-abdominal approach CASE: We discuss the case of a 72-year-old female who presented to the emergency department for a large prolapse with visible extrusion of the small bowel per vagina. The eviscerated bowel was resected by external vaginal approach due to excessive swelling of the loops which made it impossibile to reduce them through the vagina defect. A midline laparotomy was undertaken for further assessment, and the vault defect was closed by transabdominal repair CONCLUSION: From its first description in 1864, just a few cases of vaginal evisceration had been described in the medical literature; the most common organ to eviscerate is the distal ileum, although cases of omentum, colon, fallopian tube, and appendix evisceration have also been reported. We described a rare case of transvaginal evisceration of the small bowel in our emergency department; it is a rare surgical emergency that must be managed to prevent serious consequences, such as bowel ischemia and necrosis, sepsis, and death. We suggest that a multidisciplinary approach to prompt examination and management by gynaecologists and general surgeons is recommended to reduce the risk of morbidity and mortality. With this paper the authors would like to share the surgical manage of this rare emergency with other surgeons all around the world.